Interpretation of Contemporary Literature (Study of the Book of Al-Tafsîr Al-Bâyânî Li Al-Qur'ân Al-Karîm by Bint Al-Syathi') - Hanifah Ahzami (Sekolah Tinggi Ilmu Ushuluddin (STIU) Darul Hikmah, 2024)
The Qur'an is the main source of Muslims in religion, in which it contains very diverse meanings and messages, starting from that diversity has the consequences of giving birth to various interpretations, some interpreting it through linguistic approaches, science, fiqh issues, philosophy, and so on. This study discusses the method of interpretation of Bint Syathi', a female commentator from Egypt who interprets the Qur'an based on the balaghah or literary aspect. This research is a qualitative type using a descriptive-analytical approach. The results of this study found that the method used by Bint Syathi' in his interpretation was more nuanced in literature with thematic tendencies in interpreting the Qur'an. He uses a linguistic approach in analyzing the words in the Qur'an. Bint Syathi' is very concerned about the clarity and originality of the meaning of the Qur'an, his desire to catch the parrot of the Qur'an is proven by eliminating israiliyat.